Crisis hipertensiva, diabetes mellitus tipo dos obesidad en paciente femenino de 58 años - Junco Cabezas, Blanca Viviana (2019)
Hypertension is considered a serious problem worldwide that causes 9.4 million deaths annually. In Ecuador, through the ENSANUT of 2012, the prevalence of AHT in people aged 18 to 59 is more frequent in men than in women (11.2% vs. 7.5%). We present the case of a 58-year-old female patient with a personal pathological history of arterial hypertension for four years now and Diabetes mellitus II diagnosed three years ago, she says she swallows her medications at the wrong time. Through the clinical, pathological and anthropometric correlation, the diagnosis of hypertensive crisis, diabetes mellitus was reached, in which an adequate diet plan was designed for the diagnosis of hypertension and diabetes mellitus II, to improve the patient's quality of life. The case is presented below with a nutritional intervention: a 1756.3 kcal diet - hyposodic, hypocaloric, normoprotreic diet with a distribution of 50% carbohydrate macronutrients, 20% proteins, 30% fats and a fractionation of 3 main meals and 2 snacks.